PENERAPAN KUALITAS LAYANAN, KEPERCAYAAN DAN KEPUASAN SECARA ELEKTRONIK MENDORONG NIAT PEMBELIAN KEMBALI PADA TOKOPEDIA - Ilfitriah, Aniek Maschudah; Aryani, Nadillah Urfa (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
This study aims to test and analyze repurchase intention on Tokopedia through testing the level of service quality, trust and satisfaction electronically. Through the sampling technique, purposive sampling obtained electronic respondents in this study as many as one hundred and fifty-one people. This research with a quantitative approach uses the SEM-PLS analysis technique with the Smart PLS4 test tool. The hypothesis used in this study is that service quality has a significant positive effect on satisfaction, trust has a significant positive effect on satisfaction and satisfaction has a significant positive effect on repurchase intention on Tokopedia. All tests conducted on customers/respondents are carried out online (electronically). Testing using Smart PLS4 in this study to test the validity and reliability of the instruments used and stated that all statement items are valid and the research instrument (questionnaire) is stated to be reliable. The test results show that the better the quality of service to customers will increase customer satisfaction electronically. The high level of customer trust in Tokopedia will also increase customer satisfaction electronically. The higher the level of customer satisfaction encourages customers to make electronic repurchases on Tokopedia. The results of this study can be used as a reference source that Tokopedia is still the public's destination for shopping as an e-commerce platform that has the ability to provide good, quality, safe and satisfying services, especially results that can be recommended on product points and service delivery.